Fate Tracing of Isl1+Cells in Adult Mouse Hearts under Physiological and Exercise Conditions - Zhou, Yunhe; Yang, Hua; Shi, Jiahao; Zhang, Mengjie; Yang, Sai; Wang, Ning; Sun, Ruilin; Wang, Zhugang; Fei, Jian (International Journal of Sports Medicine, 2019)
Myocardial damage due to dysfunctional myocardium has been increasing, and the prognosis of pharmacological and device-based therapies remain poor. Isl1-expressing cells were thought to be progenitor cells for cardiomyocyte proliferation after specific stimuli. However, the true origin of the proliferating myocardiac cells and the role of Isl1 in adult mammals remain unresolved. In this study, Isl1-CreERT2 knock-in mouse model was constructed using CRISPR/Cas9 technology. Using tamoxifen-inducible Isl1-CreERT/Rosa26R-LacZ system, Isl1+cells and their progeny were permanently marked by lacZ-expression. X-gal staining, immunostaining, and quantitative PCR were then used to reveal the fate of Isl1+cells under physiological and exercise conditions in mouse hearts from embryonic stage to adulthood. Isl1+cells were found to localize to the sinoatrial node, atrioventricular node, cardiac ganglia, aortic arch, and pulmonary roots in adult mice heart. However, they did not act as cardiac progenitor cells under physiological and exercise conditions. Although Isl1+cells showed progenitor cell properties in early mouse embryos (E7.5), this ability was lost by E9.5. Furthermore, although the proliferation and regeneration of heart cell was observed in response to exercise, the cells associated were not Isl1 positive.
Keywords: fate tracing; Isl1; CRISPR/CAS9; aerobic exercise